THE CONCEPT OF PENAL MEDIATION FOR DEFAMATION DELICT IN THE INDONESIA ITE LAW AS A MANIFESTATION OF RESTORATIVE JUSTICE - Yaris Adhial Fajrin; Ach. Faisol Triwijaya (Faculty of Law, Universitas Sebelas Maret, 2020)
The paper aimed to analyze the position of defamation as a complaint delict in the ITE Law and the chances of applying penal mediation in the settlement of criminal defamation charges in the ITE Law. This research uses a normative legal research with qualitative analysis techniques. The research result shows that defamation in the field of ITE is a complaint delict that the settlement of the case can be done through the Alternative Dispute Resolution (ADR) outside the court through penal mediation mechanism. The settlement of criminal cases through penal mediation has been in line with the direction of the renewal of Indonesian criminal law which is moving towards improving the impact of a criminal act as part of the purpose of criminalization. Penal mediation that promotes the values of consensus deliberation is also in line with the basic values of Pancasila, to encourage peace between the conflicting parties and improve the reputation, self-esteem, and dignity of victims damaged by defamation committed by the perpetrators. The advantages of penal mediation have not been followed by the rule of law of the event that regulates specifically the procedure of penal mediation so that not a few cases of defamation are ultimately decided by criminal sanctions to the perpetrators. Therefore, the mechanism of penal mediation needs to be regulated in the Indonesian Criminal Code in the future, to provide guarantees of a fair and beneficial criminal settlement for all parties, as well as a guarantee of the right to free responsible speech.